2014
DOI: 10.3109/0886022x.2014.917561
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium excretion and hypomagnesemia in pediatric renal transplant recipients

Abstract: Patients with higher tacrolimus trough blood levels, lower glomerular filtration rate and at early posttransplant period had risk of hypomagnesemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…In hypomagnesemic patients with normal renal function, fractional magnesium excretion is a useful marker for the diagnostic approach to hypomagnesemia versus 24-hour urinary magnesium excretion. 23 In our study, 24-hour urinary magnesium excretion was within reference ranges in 64.8% of patients, but fractional magnesium excretion was higher than the normal limits. It has been reported that tacrolimus level was the best predictor of fractional magnesium excretion.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…In hypomagnesemic patients with normal renal function, fractional magnesium excretion is a useful marker for the diagnostic approach to hypomagnesemia versus 24-hour urinary magnesium excretion. 23 In our study, 24-hour urinary magnesium excretion was within reference ranges in 64.8% of patients, but fractional magnesium excretion was higher than the normal limits. It has been reported that tacrolimus level was the best predictor of fractional magnesium excretion.…”
Section: Discussionsupporting
confidence: 46%
“…In adult renal transplant recipients, the prevalence of hypomagnesemia was found to range from 10.2% to 43%. 22 Uslu Gökceoğlu and associates 23 found that the rate of hypomagnesemia in pediatric renal transplant recipients (mean age of 13.6±3.7 y) was 41% and the rate of hypermagnesuria was 65%. In our study, we found that the rate of hypomagnesemia was high in pediatric heart transplant patients versus values reported in adult renal transplant recipients, which is consistent with other pediatric studies.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst hypomagnesemia is prevalent in children following renal transplantation [11], its association with NODAT has not previously been examined.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the renal function of the children with CKD (the CKD group) was also determined with chromium-51 EDTA analysis (data not shown), which showed a significant relation with the FE Mg 2+ . Also in pediatric patients after kidney transplantation, FE Mg 2+ was negatively correlated with the renal function [ 45 , 46 ]. In adult patients, the renal function did not predict FE Mg 2+ [ 21 ].…”
Section: Discussionmentioning
confidence: 99%